Texto humorístico por uma leitura para além do riso - Alves, Jucelma Sacramento (2016)
This work does not have the aim of revolutionize the teaching of Portuguese language in the classes of Elementary School II, although it intends to offer a tool so that the subjects of the intervention can rethink the way of learning and socializing the linguistic-discursive constructions. For this, we work with the discursive genre charge because it is a multimodal genre that combines verbal language (the word) with nonverbal language (the image). Besides the multimodality that makes up the chargic text, our option for the textual genre charge is justified by discourses full of meanings and interspersed by humor. For a systematized work with the genre, a didactic sequence was developed and applied, whose objective was to verify the knowledge that the student already possessed, assisting in the development of fundamental skills to increase the reading competence of the multimodal text. Our work is divided in nine stages, dealing with conceptions of language and language, discursive genres, reading of images, methodological approach, workshop description and data analysis respectively.